Association of Endothelial Nitric Cxide Synthase(eNOS) Gene Deletion with Diabetic Mellitus Type 1 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Endothelial NOS (eNOS) is one of important antioxidant enzymes contributed in oxidative redox modulation in body researchers improved that there wear association with complicated of some diseases like diabetes mellitus, the present study was carried out to investigate relation between deletion in eNOS gene with DM  type 1 in Najaf province patients,  about 25 patients and 25 controls were collected from DM  center with data the DNA extraction to amplified eNOS gene, the results show that there were significant elevation in deletion pattern patient (84% samples) while lower in control (16%samples) at p< 0.0001, also significant differences in age and fasting blood glucose, the present study concluded that it is a strong association between deletion in VNTR  repetitive sequence and diabetic patients type 1.